Peer performance evaluations in global virtual teams: A longitudinal analysis of surface- and deep-level attributes - Tavoletti, Ernesto; Bernhard, Theresa; Dong, Longzhu; Taras, Vas (Journal of International Management, 2023)
Most research on peer performance evaluations (PPEs) has been conducted using co-located teams, assuming that PPEs are static, and focusing on the effects of PPEs, while ignoring how attributes of the evaluated individual influence PPEs, and if PPEs may vary over time. The present study advances this line of research by applying theory on impression formation and Tuckman's team stages model to explore the varying relevance of surface-level and deep-level individual attributes on PPEs across the team's life, and specifically in the context of global virtual teams (GVTs). We used longitudinal data across ten weeks of 831 individuals from 34 countries working in 239 different GVTs. We found that surface-level attributes, such as age and home country reputation, affect PPEs in the early stages of the team project, while the deep-level attributes, such as cognitive ability and English language proficiency, influence PPEs in the late phase of a GVT's life. We also found that cultural intelligence impacts PPEs relatively early on, and emotional intelligence is only relevant for PPEs when the GVT hits critical turning points, while gender influences PPEs throughout the project. We discuss the theoretical and managerial implications of our findings and provide directions for future research on PPEs in GVTs.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Categorization; Deep-level attributes; Global virtual teams; Peer evaluations; Peer performance evaluations; Surface-level attributes; X-culture; Kulturelle Vielfalt